Malaysia Toward Renewable Energy: Biogas Generation From Anaerobic Digestion of Durian Musang King Waste - Junoh H.; Rahman K.A.; Mohamed H.; Zainal B.S.; Aziz N.A.M.; Shamsuddin A.H. (American Institute of Physics, 2025)
Producing Bio-Methane gas from biomass to generate energy has been researched and studied thoroughly by many global researchers since the awakening of the importance of renewable energy. In this study, Durian Musang King's waste has been chosen as the substrate for Anaerobic Digestion (AD) to produce biogas for renewable energy. Three manipulated factors were tested in the one-week design experiment through the Bio Methane Potential (BMP) Test, namely (1) pre-treatment of substrate, (2) change in Inoculum to Substrate Ratio (ISR) and (3) change in the type of inoculum to be compared with a Standard Solution (1.05 g untreated substrate, 3:1 ISR and EM-1 inoculant as inoculum). The experiment results show that applying the pre-treatment process of grinding on Durian waste was unnecessary as there was no significant improvement in the biogas production. Using ISR 2:1 rather than 3:1 drastically increased the biogas generation from durian waste and elongated the biogas generation period. Palm Oil Mill Effluent (POME), another type of inoculum in the third experiment to compare with a commercial EM-1 Microbial Inoculant, has resulted in POME ranked below EM-1 in the total volume of biogas production. ? 2024 American Institute of Physics Inc.. All rights reserved.